Pengembangan Sistem Deteksi Kemiripian TA Berbasis Algoritma Rabin Karp & Levensthein Naskah Skripsi Mahasiswa JTIK - M, Trisman; Haripuddin, Haripuddin; Sanatang, Sanatang (Rifa'Institute, 2023)
This research is a software development research that aims to create a reading detection system for student thesis in the Department of Informatics and Computer Engineering, Makassar State University using the PHP programming language with the Laravel Framework. The technique used to retrieve data from the web is using CURL from PHP. This study uses a prototype development model with stages: requirements gathering, rapid design, prototype evaluation by users, large-scale design, testing, and system implementation. Data was collected using documentation, observation and questionnaire techniques. The system is validated by two system experts. Data analysis used descriptive statistical analysis techniques. Based on the research results, a system was produced that could be used to check the correctness of documents properly. Based on the test results using the ISO 25010 quality standard, the plagiarism system has met the standards where: (a) The functionality aspect has a value of 1 (Very Good) (b) The performance aspect obtained a performance value of 83.71% (Grade B) and time response 2.2 seconds (Accepted); (c) The portability aspect obtains a portability score of 1 (Very Decent); (d) the usability aspect obtained a usability level of 86.27% (Very Good); (e) The Reliability aspect obtains a proportion per test value of 100%, this indicates that the system being developed has high reliability; (f) Compatibility Aspect This characteristic measures the extent to which a product, system or other component; and (g) Security aspect, the acquisition of test scores from the immune scanner shows that the system security level is at level C so that it can be concluded that the security level of this system is in the Good category. Based on the research results of the TA reasoning selection system based on the Rabin-Karp & Levensthein thesis script of JTIK students after being validated and tested using the ISO 25010 standard, it can be concluded that all aspects tested have met software quality standards. The results of this test have shown the quality assurance of the product being developed so that it can be stated that this system is feasible to use.